2020
DOI: 10.1111/wre.12447
|View full text |Cite
|
Sign up to set email alerts
|

Control ofAilanthus altissimausing cut stump and basal bark herbicide applications in an eighteenth‐century fortress

Abstract: Ailanthus altissima (Mill.) Swingle (tree of haven) is an arboreous plant belonging to the Simaroubaceae family. Native to China and North Vietnam, this species has by now spread to all the continents, except Antarctica. It is considered one of the most invasive plants (Weber and Gut, 2004), it can easily grow on different substrates, and it tolerates air pollution, dry conditions and high concentrations of salt and heavy metals (Kowarik and Säumel, 2007; Sladonja et al., 2015). It is a shade-intolerant specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The remaining upper portion of the plant would then slowly die over time while still upright, although the stems of several larger plants fell over and died lying on the ground. Differences in response of small and large woody plants to basal bark treatments are not uncommon, with smaller plants generally more susceptible [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining upper portion of the plant would then slowly die over time while still upright, although the stems of several larger plants fell over and died lying on the ground. Differences in response of small and large woody plants to basal bark treatments are not uncommon, with smaller plants generally more susceptible [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both the traditional and thinline basal bark methods are used to control invasive woody weeds [ 22 , 23 , 24 , 25 , 26 ]. In the current study, they provided similar efficacy and either could be used depending on the preference of the operator.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when comparing mechanical versus chemical, it was found a mortality of 21.3% by manual cutting versus near total control with different herbicides [70]. Other authors have demonstrated that herbicides such as glyphosate, imazapyr, picloram, triclopyr, or 2.4-D had better control than mechanical methods alone [21,71,72]. When comparing cutting versus herbicide application over the cut stump with glyphosate, imazapyr, or triclopyr, trees without herbicide produced more resprouts than trees with herbicide [73].…”
Section: Mechanicalmentioning
confidence: 99%
“…The rapid entry into flowering (fourth year), the huge amount of seed production, the wind dispersal, and the vegetative reproduction favor its expansion and enhance its persistency [7]. Its ecological preference for altered and degraded ecosystems and its well-developed root system make this species frequent in communication corridors such as railways, freeways, or walkways [2], in which it damages constructions and pavements and reduces visibility [18], in rural areas along fencerows, woodland edges, or forest openings [2], and in heritage areas such as archaeological monuments, degrading them [19][20][21][22]. But, apart from physical damage, this species has allelopathic effects.…”
Section: Introductionmentioning
confidence: 99%
“…A. altissima is a deciduous treed belonging to the family Simaroubaceae and native to Southeast Asia and India. Due to its ornamental value, this plant has been widely cultivated in Africa, Oceania, and Europe ( Zhang et al, 2007a , Zhang et al, 2007b , Fogliatto et al, 2020 ) but it can be found in several countries across Europe and North America. It has been widely used to treat ophthalmic illnesses, ascariasis, spermatorrhea, bleeding, asthma, and epilepsy ( Yang et al, 2014 , Kim et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%